Final results from the EU focal impulse and rotor modulation (E-FIRM) registry. (24th May 2021) - Sommer, P; Spitzer, S; Brachmann, J; Janssen, G; Lenz, C; Luik, A; Sarver, A; Szili-Torok, T
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: The exact pathophysiology of how pulmonary vein (PV) triggers initiate or maintain episodes of atrial fibrillation (AF) has been elusive. Catheter ablation at relatively circumscribed areas of rapidly spinning rotors or very rapid focal impulse formation can significantly affect AF. Targeted ablation of these sources using Focal Impulse and Rotor Modulation (FIRM™) shows promise. Purpose: To assess the safety and effectiveness of FIRM-guided procedures for the treatment of any type of symptomatic atrial fibrillation (AF). Methods: Two hundred and ninety-nine subjects were enrolled in the E-FIRM Registry at 9 clinical sites in Germany and the Netherlands. Subjects were eligible if they had reported incidence of at least 2 documented episodes of symptomatic AF during the preceding 3 months and had failed at least Class I or III anti-arrhythmia drug. Data was collected at enrollment/baseline, procedure, and at 3-, 6-, and 12-month follow-up visits. Results: A majority (59.5%, 178/299) had a history of previous ablation, 81.1% (133/164) in the left side, with an average of 1.5 ± 0.8 [range 0, 5] prior ablations. The primary safety endpoint was defined as freedom from procedure related Serious Adverse Events (SAEs) through 7-days and at 12-months. At 7-days, freedom from procedure related SAEs was 94.8% (257/271). At 12-months, freedom from procedure related SAEs was 84.4% (184/218). There were no deaths. Acute effectiveness success, defined as the elimination of all identified rotors, occurred in 64.0% (165/258) of treated patients. All patients for which data was reported had at least 1 rotor identified. The most common regions to find rotors were the lateral wall of the right atrium, the anterior/septal wall of the left atrium, and the posterior inferior region of the left atrium. 75.2% (194/258) of patients had at least one rotor identified in the right atrium, and 84.1% (217/258) of patients had at least one rotor identified in the left atrium. Success was defined as two sequential endpoints: single procedure freedom from AF recurrence at 3-months and single procedure freedom from AF recurrence. At 12-months, success was achieved in 46.4% (13/28) Paroxysmal, 42.9% (87/203) Persistent, and 0% (0/9) Long Standing AF subjects. Conclusions: Since acute success was reported as being achieved in only ∼2/3 of the treated subjects, it is possible that the full potential benefit of the FIRM-guided ablation was hidden in this evaluation of the full cohort. Considering the previous ablation and disease history of subjects, a single-procedure success rate at 12-months over 40% was considered a positive result. Based on these results, FIRM-guided RF ablation in conjunction with conventional RF ablation practices is both a safe and effective treatment strategy for patients with symptomatic AF.